2008
DOI: 10.1111/j.1467-6494.2008.00542.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Dispositional Traits in Accounting for Country and Ethnic Group Differences on Adjustment

Abstract: Country and ethnic group differences on adjustment have been demonstrated numerous times, and the source of these differences has been typically interpreted as cultural. We report two studies in which country (Study 1) and ethnic group (Study 2) differences on depression, anxiety, optimism versus pessimism, well-being, and self-esteem are mediated by dispositional traits. These findings provide an alternative explanation for previously reported country and ethnic group differences on these variables and encour… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 86 publications
0
5
0
Order By: Relevance
“…Since we used nationally representative data from German adults, the generalization of our findings to younger participants (<18 years) and other cultures is limited. Cultural differences are known for the associations of neuroticism (Matsumoto et al, 2009) and specific emotion regulation strategies (Schunk et al, 2021; Schunk et al, 2022) with well‐being and social adaptation. Further, individuals' level of neuroticism was shown to be more flexible over time in non‐Western cultures (Chopik & Kitayama, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Since we used nationally representative data from German adults, the generalization of our findings to younger participants (<18 years) and other cultures is limited. Cultural differences are known for the associations of neuroticism (Matsumoto et al, 2009) and specific emotion regulation strategies (Schunk et al, 2021; Schunk et al, 2022) with well‐being and social adaptation. Further, individuals' level of neuroticism was shown to be more flexible over time in non‐Western cultures (Chopik & Kitayama, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In Colombia, the mean HADS-anxiety and depression scores were 4.0 ± 3.4 and 4.7 ± 3.9 in healthy men aged > 60 years, respectively [28]. One study showed severer depression among Japanese individuals compared to Americans [29]. Further, patients in the present study displayed more depression but less anxiety than did Brazilian patients with the same disease (5.9 ± 4.2 and 7.9 ± 4.7, respectively) [17].…”
Section: Discussionmentioning
confidence: 99%
“…Work on values, attitudes, beliefs, and personality traits often involves attempts to measure such enduring characteristics (Bond et al, 2004;K. Leung & Bond, 2009;Matsumoto, 2006;Matsumoto, Nakagawa, & Estrada, 2009;Schwartz, 1994). Some work emphasizing the independent versus interdependent self also takes this perspective because these models of self come to organize the way people chronically approach the world (Singelis, 1994).…”
Section: Snapshots Of a Larger Processmentioning
confidence: 99%